Factors Associated with Episiotomy Practices in Bahirdar City, Ethiopia: A Cross-Sectional Study - Beyene F; Nigussie AA; Limenih SK; Tesfu AA; Wudineh KG (Dove Medical Press, 2020)
Fentahun Beyene, Azezu Asres Nigussie, Simachew Kassa Limenih, Azimeraw Arega Tesfu, Kihinetu Gelaye Wudineh Department of Midwifery, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, EthiopiaCorrespondence: Fentahun Beyene Email yenefenta84@gmail.comBackground: Episiotomy is the surgical enlargement of the vaginal orifice during the last part of the second stage of labor or childbirth by an incision to the perineum. The World Health Organization advises the use of episiotomy on a restricted and selective basis. Indeed, the rate of episiotomy in developed countries is decreasing, but in developing countries, including Ethiopia, it still remains high. Therefore, this study tried to assess the proportion and factors associated with episiotomy among women who gave birth at Felege Hiwot Referral Hospital, Bahir Dar City, North West Ethiopia, 2017.Methods: An institution-based cross-sectional study was conducted among 411 mothers from February to April 2017. Data were collected through face-to-face interviews and supported by observation using standard checklist with systematic random sampling technique. Data was entered by Epi Info and analyzed by SPSS version 23. The association between variables was analyzed using bivariable and multivariable logistic regression model. P-value < 0.05 at 95% CI was considered to be statistically significant.Results: The proportion of episiotomy was 41.1% with 95% CI (36.5%, 46.2%). Multivariable logistic regression showed that primiparity (AOR=6.026, 95% CI (3.542,10.253)), prolonged second stage of labor (AOR=4.612, 95% CI (2.247,9.465)), instrument delivery (AOR =3.933, 95% CI (1.526,10.141)), using oxytocin (AOR=2.608, 95% CI (1.431,4.751)), medical resident attendant (AOR =3.225, 95% CI (1.409,7.382)) and birth weight ≥ 4000 grams (AOR=5.127,95% Cl (1.106,23.772)) were significantly associated with episiotomy practice.Conclusion: The proportion of episiotomy was high. Parity, using oxytocin, second-stage labor duration, instrument delivery, birth weight, and delivery attendant were statistically significant factors for episiotomy practice. Therefore, as per our findings, we suggest awareness creation, and the setting and use of new national guidelines, the practice of routine episiotomy should be abandoned, and selective and restrictive use of episiotomy is highly advised.Keywords: episiotomy, women, Bahir Dar, Ethiopia